2017
DOI: 10.4172/2332-2543.1000195
|View full text |Cite
|
Sign up to set email alerts
|

First Confirmed Record of Striped Hyaena (Hyaena hyaena) Den in Nepal

Abstract: Hyaena is one of the twenty seven mammals species protected by National Park and Wildlife conservation ACT-1973 of Nepal. Study of hyaena is lacking in Nepal so less information is available about this species in country. A single den was recorded in Kalapani community forest of Deukhuri Valley in Dang District located at the elevation of 282m above sea level. Signs, camera trap images and video confirm the den of striped hyaena which is first confirmed record of Hyaena den in Nepal. [3][4][5] where water is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…We reviewed key literature to understand den‐site selection in carnivores and other mammals, and to identify the best approaches for this study (Bopanna, 2013; Boydston et al., 2006; Chourasia et al., 2020; Davies et al., 2016; Jackson et al., 2014; Khanal et al., 2017; Majumder et al., 2016; Mandal, 2018; Mukherjee et al., 2018; Nikunj et al., 2009; Singh et al., 2010; Singh et al., 2014; Vroom et al., 1980). Furthermore, data on the attributes of potential den sites for striped hyaenas were collected post‐identification of critical microhabitat features.…”
Section: Methodsmentioning
confidence: 99%
“…We reviewed key literature to understand den‐site selection in carnivores and other mammals, and to identify the best approaches for this study (Bopanna, 2013; Boydston et al., 2006; Chourasia et al., 2020; Davies et al., 2016; Jackson et al., 2014; Khanal et al., 2017; Majumder et al., 2016; Mandal, 2018; Mukherjee et al., 2018; Nikunj et al., 2009; Singh et al., 2010; Singh et al., 2014; Vroom et al., 1980). Furthermore, data on the attributes of potential den sites for striped hyaenas were collected post‐identification of critical microhabitat features.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, many cases regarding sightings of striped hyena and humanhyena encounters are frequently reported in Nepal. Khanal et al (2017) reported that a den of striped hyena was found in the Kalapani community forest of Deukhuri valley in Dang district in 2012. The den found was located at an altitude of 282 m from sea level and was recorded as the first confirmed den of striped hyena in Nepal and in 2017, striped hyenas residing in that den were confirmed to be breeding which was found out through camera trapping (Khanal et al, 2017).…”
Section: Population Statusmentioning
confidence: 99%
“…Khanal et al (2017) reported that a den of striped hyena was found in the Kalapani community forest of Deukhuri valley in Dang district in 2012. The den found was located at an altitude of 282 m from sea level and was recorded as the first confirmed den of striped hyena in Nepal and in 2017, striped hyenas residing in that den were confirmed to be breeding which was found out through camera trapping (Khanal et al, 2017). Exact population data is lacking because no particular research has been carried out for the population study and only guessed estimated data is available (Jnawali et al, 2011).…”
Section: Population Statusmentioning
confidence: 99%
See 1 more Smart Citation